Analysis Of The Level Of Satisfaction And Quality Of Excellent Service Clearance In Out At Pt. Adira Shipping Management - Hanik, Kumila; Yulianto, Andri; Ningrum, Riza Setyo; Maharani, Atria (PT. Riset Press International, 2024)
Excellent service is an attempt to serve the needs of others by providing the best service. This study aims to test the hypothesis that there is an influence on the level of satisfaction and quality on excellent service, whether it affects the trust obtained, the effect of the level of satisfaction obtained on excellent service and agent quality on excellent service, and the effect of satisfaction level and quality on excellent service clearance in/out. This research is a survey research. The population in this study were all ships that had been agented by PT. Adira Shipping Management. The sampling technique used purposive sampling with a total sample of 60 crew members. The data analysis technique used is multiple regression. The results showed that there was a positive influence on the level of satisfaction with excellent service clearance in/out as evidenced by the tcount of 2.189, a significance value of 0.033>0.05 and a regression coefficient of 0.266. There is a positive effect of quality on excellent service clearance in/out as evidenced by the tcount of 3.932, a significance value of 0.000> 0.05 and a regression coefficient of 0.374; and finally there is the influence of the level of satisfaction and quality on clearance in/out excellent service with a Fcount of 56.731 and a significance of 0.000 <0.05.